2007
DOI: 10.1128/iai.00341-07
|View full text |Cite
|
Sign up to set email alerts
|

Adherence-Inhibitory Intestinal Immunoglobulin A Antibody Response in Baboons Elicited by Use of a Synthetic Intranasal Lectin-Based Amebiasis Subunit Vaccine

Abstract: We designed an amebiasis subunit vaccine that is constructed by using four peptide epitopes of the galactose-inhibitable lectin heavy subunit that were recognized by intestinal secretory immunoglobulin A (IgA) antibodies from immune human subjects. These epitopes are contained in the region encompassing amino acids 758 to 1134 of the lectin heavy subunit, designated LC3. Baboons (Papio anubis) are natural hosts for Entamoeba histolytica; naturally infected baboons raised in captivity possess serum IgA antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Notably, a vaccination schedule of four doses of 1600 μ g peptide/nostril in combination with cholera toxin as adjuvant once a week was able to eradicate amoebic infection in all baboons by the 51st day after intracecal challenge with trophozoites. Moreover, serum IgG and IgA antibodies induced by natural infection of baboons with E. histolytica are directed to epitopes present in the LC3 fragment of the Gal-lectin, and this immunodominance is shared with humans carrying asymptomatic E. histolytica infection or recently cured of ALA [ 14 ]. These results, together with the obtained by our group, previously and reported here, using recombinant baculoviruses driving the expression of the LC3 fragment [ 17 ] as well as other protection assays using LC3 as immunogen [ 15 ], highly support that Gal-lectin, in particular its LC3 fragment, is the target of protective antibodies and cellular immune responses resolving intra- and extraintestinal amoebiasis, and, therefore, it should be the basic component of an effective vaccine against human amoebiasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, a vaccination schedule of four doses of 1600 μ g peptide/nostril in combination with cholera toxin as adjuvant once a week was able to eradicate amoebic infection in all baboons by the 51st day after intracecal challenge with trophozoites. Moreover, serum IgG and IgA antibodies induced by natural infection of baboons with E. histolytica are directed to epitopes present in the LC3 fragment of the Gal-lectin, and this immunodominance is shared with humans carrying asymptomatic E. histolytica infection or recently cured of ALA [ 14 ]. These results, together with the obtained by our group, previously and reported here, using recombinant baculoviruses driving the expression of the LC3 fragment [ 17 ] as well as other protection assays using LC3 as immunogen [ 15 ], highly support that Gal-lectin, in particular its LC3 fragment, is the target of protective antibodies and cellular immune responses resolving intra- and extraintestinal amoebiasis, and, therefore, it should be the basic component of an effective vaccine against human amoebiasis.…”
Section: Discussionmentioning
confidence: 99%
“…The gal-lectin, with its cysteine-rich portion of the 170 kDa lectin subunit, is the target for serum of 95% of patients with amoebic liver abscess [ 9 ] as well as IgG and IgA anti-Gal-lectin antibodies recovered from serum and feces of patients with intestinal amoebiasis, respectively [ 10 , 11 ]. Oral or nasal immunization of mice, gerbils, and nonhuman primates with the cystein-rich section of galactose-inhibitable lectin LC3 and cholera toxin as adjuvant induced high level of specific serum IgG and fecal IgA [ 12 , 13 ] antibodies that inhibit in vitro E. histolytica adherence to CHO cells [ 14 ]. Moreover, intraperitoneal immunization of gerbils with the LC3 fragment with Titermax adjuvant elicited IgG antibodies that conferred 71% of protection against ALA [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…During laparotomy, an inflammatory mass involving the right colon was confirmed, and a right hemicolectomy was performed. Nitroimidazoles, particularly tinidazole, are the mainstay therapy for invasive amoebiasis ( Abd Alla et al ., 2007 ); metronidazole is the most commonly available drug for treatment. The cure rate with this therapy is >90 % ( Lasserre et al ., 1983 ).…”
Section: Outcome and Follow-upmentioning
confidence: 99%
“…A vaccine containing the native Gal/GalNAc lectin of E. histolytica shows protective effect against amebic colitis and liver abscess in animal models (Petri and Ravdin, ; Houpt et al ., ; Ivory and Chadee, ). It was also shown that a Gal/GalNAc lectin‐based synthetic peptide vaccine administered intranasally successfully elicited an adherence‐inhibitory intestinal anti‐lectin IgA antibody response and was effective in preventing amebic colitis in baboons (Abd Alla et al ., 2007; 2012). These studies are an illustration of the translation of a clinical observation (that IgA anti‐lectin is associated with protection) to experimental development of vaccines (reviewed in Quach et al ., ).…”
Section: Discoveries From the Collaboration Research Between Clinic Amentioning
confidence: 99%